2009
DOI: 10.2109/jcersj2.117.258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron content and annealing temperature on the color characteristics of Fe-ZrSiO4 coral pink pigments synthesized by Sol-gel method

Abstract: To investigate color properties by inclusion of hematite in the iron zircon pigments, different samples were prepared by the sol-gel method without mineralizer. The starting amount of the ferric salt in the sol-gel reacting mixture was varied in order to obtain Fe2O3/Zr molar ratio in the range of 5-30%. Fe-ZrSiO4 pigments of the sol-gel reaction were calcined the range 600-1300°C. The crystalline phases were determined by using X-ray diffraction(XRD). The process of inclusion of hematite in iron zircon pink c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
2
6
0
3
Order By: Relevance
“…49 K.-R. Pyon and B.-H. Lee investigated the effect of iron as a dopant by varying its concentration from 5−30% and concluded that all the investigated compositions resulted in the formation of mixture of multiple phases, namely, α-Fe 2 O 3 , ZrSiO 4 , t-ZrO 2 , m-ZrO 2 , and c-SiO 2 at 1300 °C. 50 Herrera et al obtained solid solution of iron doped ZrSiO 4 at 1100 °C, and they also demonstrated that Fe 3+ has occupied the tetrahedral lattice of ZrSiO 4 by replacing Si 4+ ions. 46 The present study investigates the varying concentrations of Fe as a dopant ranging from 5% to 100% in SiO 2 −ZrO 2 binary oxide system.…”
Section: ■ Discussionmentioning
confidence: 99%
“…49 K.-R. Pyon and B.-H. Lee investigated the effect of iron as a dopant by varying its concentration from 5−30% and concluded that all the investigated compositions resulted in the formation of mixture of multiple phases, namely, α-Fe 2 O 3 , ZrSiO 4 , t-ZrO 2 , m-ZrO 2 , and c-SiO 2 at 1300 °C. 50 Herrera et al obtained solid solution of iron doped ZrSiO 4 at 1100 °C, and they also demonstrated that Fe 3+ has occupied the tetrahedral lattice of ZrSiO 4 by replacing Si 4+ ions. 46 The present study investigates the varying concentrations of Fe as a dopant ranging from 5% to 100% in SiO 2 −ZrO 2 binary oxide system.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The colorant, such as carbon, was encapsulated by ZrSiO 4 to prevent to be oxidized, resulting in the good chromophoric performance and stability in the basic glaze [11,12]. Kinds of preparation M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 methods have been reported for the synthesis of the inclusion pigment, such as solid phase reactions [13,14], precipitation method [15], hydrothermal method [16] and hydrolytic sol-gel method [17,18], etc. Nevertheless, the above mentioned methods have many disadvantages, such as high calcining temperature, low encapsulation rate and complicated operation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several authors have studied different topics referred to the structural and chemical characteristics of Fe-ZrSiO 4 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . The mechanism of formation, the chemical state, and location of Fe cation in the zircon structure, the actual presence of segregated hematite and dissociation of zircon [25][26][27] have been considered as main topics.…”
Section: Introductionmentioning
confidence: 99%